2020
DOI: 10.3390/antiox9090771
|View full text |Cite
|
Sign up to set email alerts
|

Chebulic Acid Prevents Methylglyoxal-Induced Mitochondrial Dysfunction in INS-1 Pancreatic β-Cells

Abstract: To investigate the anti-diabetic properties of chebulic acid (CA) associated with the prevention of methyl glyoxal (MG)-induced mitochondrial dysfunction in INS-1 pancreatic β-cells, INS-1 cells were pre-treated with CA (0.5, 1.0, and 2.0 μM) for 48 h and then treated with 2 mM MG for 8 h. The effects of CA and MG on INS-1 cells were evaluated using the following: 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay; glyoxalase 1 (Glo-1) expression via Western blot and enzyme activity assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
2
3
0
Order By: Relevance
“…Upregulation of Glo-1 reduced hyperglycemia-induced carbonyl stress, AGE accumulation, and oxidative stress in diabetic rats (35). Similar to previous studies (26)(27)(28)(29), Glo-1 expression was markedly suppressed in NIT-1 cells following MG treatment, which promoted intracellular accumulation of MG. The results showed that Glo-1 silencing increased the intracellular concentration of MG and further reduced METTL3 expression and m 6 A RNA levels.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Upregulation of Glo-1 reduced hyperglycemia-induced carbonyl stress, AGE accumulation, and oxidative stress in diabetic rats (35). Similar to previous studies (26)(27)(28)(29), Glo-1 expression was markedly suppressed in NIT-1 cells following MG treatment, which promoted intracellular accumulation of MG. The results showed that Glo-1 silencing increased the intracellular concentration of MG and further reduced METTL3 expression and m 6 A RNA levels.…”
Section: Discussionsupporting
confidence: 85%
“…Glo-1 is the main component of the glyoxalase system and is essential for MG detoxification in all mammalian cells (7). Similar to previous studies (26)(27)(28)(29), MG treatment decreased Glo-1 expression in NIT-1 cells (Figures 4A, B). Interestingly, Glo-1 knockdown further reduced METTL3 expression (decreased by 50.2% versus MG treated, p < 0.05; Figures 4A, C) and m 6 A RNA levels (decreased by 52.3% versus MG treated, p < 0.05; Figure 4E) in MG-treated NIT-1 cells.…”
Section: Effects Of Glo-1 Knockdown On Mettl3 Expression and M 6 A Le...supporting
confidence: 86%
“…Methylglyoxal (MGO) is primarily generated endogenously as a by-product from glycolysis by the nonenzymatic degradation of triose phosphates, such as glyceraldehyde 3-phosphate and dihydroxyacetone-phosphate and exogenously due to autoxidation of sugar, the Maillard reaction, degradation of lipids, and fermentation during food and drink processing. Formation of MGO accounts for only 0.1% of glucotriose flux with a rate of about 125 μmol/kg cell mass per day under physiological conditions. Increasing evidence indicates that MGO, containing two reactive carbonyl groups, is the leading cause (20 000 times more reactive than glucose) for the formation of advanced glycation end products (AGEs) by binding to and modifying arginine, lysine, and cysteine residues in organisms. , Over the last few decades, AGEs and MGO have received increasingly more attention and been recognized as pathogenetic mediators in chronic diseases, including diabetes, diabetic complications, , cardiovascular disease, Alzheimer’s disease, and so on. Multiple therapeutic options are available to trap MGO or prevent the formation and accumulation of AGEs or alleviate MGO/AGE-induced chronic diseases .…”
Section: Introductionmentioning
confidence: 99%
“…Glo-1 decrease was also observed after 8 h treatment with 2 mM MG (2-8 h) in rat INS-1 pancreatic Beta-cells (Yoo et al, 2020) and after 24 h treatment with 500 μM of MG in primary cultures of cerebellar neurons from P5 C57/BL6 mice (Frandsen & Narayanasamy, 2017).…”
Section: Neuronal Markers Evaluation After Mg Exposure (Nse and Map-2)mentioning
confidence: 76%
“…For instance, MG either induced or impaired the glyoxalase system in immortalized mouse hippocampal HT22 cells (Dafre et al, 2015): 300 μM MG produced an increase in Glo‐2 expression at 24 h, and a decrease in Glo‐1 activity after 24 h exposure to 750 μM MG. A significantly decrease of Glo‐1 levels or its protein expression was also observed in several in vitro studies, and once again, this effect was induced by high MG concentrations, that is, 400 μM MG after 48 h in SK‐N‐MC cells (Suh et al, 2022), and 500 μM after 24 h treatment in SH‐SY5Y (Tseng et al, 2019), as forecastable when using human neuroblastoma cell line. Glo‐1 decrease was also observed after 8 h treatment with 2 mM MG (2–8 h) in rat INS‐1 pancreatic Beta‐cells (Yoo et al, 2020) and after 24 h treatment with 500 μM of MG in primary cultures of cerebellar neurons from P5 C57/BL6 mice (Frandsen & Narayanasamy, 2017).…”
Section: Discussionmentioning
confidence: 88%